The Impact of Sustainable Energy on Liquidity and Financial Performance of the Textile Industry. (December 2022) - Asif, Rabia; Fiaz, Muhammad; Zulfiqar, Zunaina
Sustainable energy is considered to be the most important input for any organization owing to its noteworthy impact on the liquidity and performance of the firms. Hence, it is imperative to evidence the impact of sustainable energy on a firm's liquidity and performance. As the disruptions in sustainable energy adversely impact the performance of manufacturing firms by reducing production directly and amplifying operational leverage, it is significant to investigate the impact the sustainable energy on a firm's liquidity and performance. Further, the impact of disruptions in sustainable energy is size specific, therefore, the study also assumes the moderating role of firm size in shaping the stated relation. So, the aim of the current research is to investigate the impact of sustainable energy supply on liquidity and performance of the firms keeping in view the moderation effect of firm size. Using financial data of 120 textile firms from the year 2010 to 2022, the current investigation has employed a panel data methodology to quantify the impact of the sustainable energy disruption on a firm's liquidity and performance. The results revealed that the sustainable supply of energy sources significantly impacts liquidity and working capital management as well as the performance of the textile sector in Pakistan. Further, firm size tends to moderate the relation between sustainable energy supply and performance. Although the effect is found to be partially moderated. It is recommended that in the long run, the firms might opt for alternate energy sources resulting in savings from huge performance losses. Encouraged by the inadequacy of empirical evidence in developing economies like Pakistan and keeping in view the importance of working capital management and performance efﬁciency, the current work is the need of the day. The impact of sustainable energy sources must be researched to gauge the impact on the manufacturing industry's performance.